Identification and characterization of a novel GNAT superfamily Nα‐acetyltransferase from Salinicoccus halodurans H3B36 - Xiaochen Ma; Kai Jiang; Cheng Zhou; Yanfen Xue; Yanhe Ma (Microbial Biotechnology, 2022)
Summary Nα‐acetyl‐α‐lysine was found as a new type of compatible solutes that acted as an organic cytoprotectant in the strain of Salinicoccus halodurans H3B36. A novel lysine Nα‐acetyltransferase gene (shkat), encoding an enzyme that catalysed the acetylation of lysine exclusively at α position, was identified from this moderate halophilic strain and expressed in Escherichia coli. Sequence analysis indicated ShKAT contained a highly conserved pyrophosphate‐binding loop (Arg‐Gly‐Asn‐Gly‐Asn‐Gly), which was a signature of the GNAT superfamily. ShKAT exclusively recognized free amino acids as substrate, including lysine and other basic amino acids. The enzyme showed a wide range of optimal pH value and was tolerant to high‐alkali and high‐salinity conditions. As a new member of the GNAT superfamily, the ShKAT was the first enzyme recognized free lysine as substrate. We believe this work gives an expanded perspective of the GNAT superfamily, and reveals great potential of the shkat gene to be applied in genetic engineering for resisting extreme conditions.